2018
DOI: 10.1177/0218492318777394
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and paradoxical coronary embolism with a patent foramen ovale

Abstract: Paradoxical embolism through a patent foramen ovale is a very unusual event considering that this cardiac anomaly may be present in as much as 26% of the general population. We describe the case of a 68-year-old man with a pulmonary and paradoxical coronary embolism in the presence of a patent foramen ovale. The finding of a worm-shaped thrombus though the atrial septum together with the risk of further embolization through the atrial septum prompted surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…Several previous studies 31,32 have shown that smoking is closely related to atherosclerosis and thrombosis. Long-term heavy smoking can damage alveolar epithelial cells, resulting in a reduction in the amount of oxygen diffused.…”
Section: Discussionmentioning
confidence: 96%
“…Several previous studies 31,32 have shown that smoking is closely related to atherosclerosis and thrombosis. Long-term heavy smoking can damage alveolar epithelial cells, resulting in a reduction in the amount of oxygen diffused.…”
Section: Discussionmentioning
confidence: 96%
“…Aspiration thrombectomy; Intracoronary heparin and abciximab; Antiplatelet treatment not mentioned Pul: Lifelong anticoagulant (Warfarin) PFO closure: Multidisciplinary discussion not recommend 4 Smith et al [ 10 ] 69 years female STEMI (inferior wall); PE; PFO; Acute RV Failure C: Occlusion of PD and PL; Aspiration thrombectomy and balloon dilation; Oral aspirin Pul: Pulmonary angiography, interventional clot fragment and aspiration; and intra-arterial thrombolysis; Long-term anticoagulant (Warfarin) PFO closure: No 5 Knobloch et al [ 13 ] 38 years male STEMI (inferior wall); PE and DVT. Embolic occlusion of the left popliteal artery and left carotid artery; PFO C: Normal coronary angiogram Pul: Not mentioned PFO closure: Yes, transcatheter Others: Left popliteal: Embolus removal with Fogarty catheter; Left carotid embolus: surgery 6 Haghi et al [ 14 ] 61 years female NSTEMI; PE; PFO C: Balloon angioplasty (OM) and oral Aspirin Pul: Long-term anticoagulant (Warfarin) PFO closure: No 7 Falcetta et al [ 15 ] 68 years male STEMI (inferior wall); PE and DVT; PFO. C: Aspiration thrombectomy (RCA) Pul: Surgical removal of embolus in pulmonary trunk; Long-term anticoagulant (Specific drug not mentioned) PFO closure: Surgery removal of the worm-shaped embolus (13 cm) and PFO surgical sutured 8 Uchida et al [ 16 ] 59 yrs male STEMI (inferior wall); PE; PFO; AF.…”
Section: Discussionmentioning
confidence: 99%
“…По данным Шведского регистра, они встречались примерно у 10% у пациентов с ТЭЛА. При этом у 36% пациентов с выявленным тромбом в правом предсердии находились признаки ТЭЛА [7]. Как уже упоминалось выше, существует несколько подходов к лечению тромбоза предсердий: механическое удаление и медикаментозное лечение (тромболизис или антикоагулянт) [8].…”
Section: что делать с тромбом в полости сердца?unclassified